Digital Marketing, Packacing dan Branding Hasil Pertanian Desa Karangtawar Kecamatan Laren Kabupaten Lamongan - Eny Latifah; Diva Ayu Pramiswari; Aicha Widia Dzilfachriah; Arina Faridatul Mahmudah; Alya Khoioni Muhibbah; Saibatul Fauziyah; Suhailah Suhailah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This Community Service aims to provide assistance to the people of Karangtawar Village, especially farmers, by providing training in digital marketing, packaging and branding of existing agricultural products. The method used is Participatory Action Research (PAR) where in our actions we involve the community so that solutions to existing problems can be identified. The results of Community Service are Digital Marketing training in the form of: Creating Social Media Facebook, Instagram and e-Commerce Platforms such as Shopee, Lazada. Packaging takes the form of: product packaging that is more attractive than before in order to increase sales results and people's income. Branding takes the form of: creating a brand logo for agricultural products using the CANVA application to be implemented in Karangtawar Village, Laren District, Lamongan Regency.